GENETIC DIVERGENCE IN NIGERIA AND INDIA PEARL MILLET ACCESSIONS BASED ON AGRONOMIC TRAITS AND GRAIN YIELD CHARACTERS - ANIMASAUN, David Adedayo; Morakinyo, Joseph A; Krishnamurthy, Ramar; Mustapha, Oba T (Journal of Agricultural Sciences (Belgrade), 2017)
The study assessed genetic diversity in Nigeria and India accessions of peal millet based on morpho-agronomic traits to identify accessions with superior characters which could be utilized in breeding programs. Twenty-four pearl millets accessions were grown in the screenhouse in five replicates and evaluated for two seasons. Data collected on the accessions using standard descriptors were analysed statistically. There were significant variations for characters studied among the accessions. IP22281 had highest mean plant height (108.90 cm) while NGB00531 recorded the least (61.02 cm). Significant intra-specific variation exits in number of leaf/plant, leaf length, leaf width, number of nodes and internode length, however, stem girth was similar for the accessions. Tillering was generally poor with highest (1.60 tiller/plant) found in NGB00531. Significant positive correlation occurred between plant height, number of leaves, leaf length and width. Panicle emerged between 44.72-56.91 days and NGB00548 had shortest maturity time. Also, panicle length and diameter varied significantly for the accessions. Highest grain yield and weight/1000grain was recorded in NGB00616 and the least in IP22269. The principal component analysis partitioned the accessions into four clusters, consisting mixtures of Nigerian and Indian members. Similarly, the dendrogram grouped the accessions into two main groups which are sub-divided into smaller clusters of Nigeria and India accessions in the same cluster. The study concludes that variations in morpho-agronomic and yield characters among the accessions studied could be harnessed for the crop improvement. Clustering pattern of thes accessions indicates they are genetically related and possibly from same progenitor but could have be separated by geographical or ecological isolation mechanism.